Management of Independent Business-Based Private Madrasah Development at Madrasah Aliyah - Mahadin Shaleh; Andi Riawarda; Ummung Kallang (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2019)
This research aimed to know determine the management development of Madrasah Aliyah As'adiyah No. 16 Abbreviation Sabbang District, North Luwu Regency; To find out the management of independent business development at Madrasah Aliyah As'adiyah No. 16 Abbreviation Sabbang District, North Luwu Regency; To know the management of development of Madrasah Aliyah As'adiyah No. 16 Abbreviation Sabbang District, North Luwu Regency, is based on independent business. This research is qualitative descriptive; the data collection techniques used in this research are observation techniques, interviews, documentation, data analysis used is data reduction, data presentation, and concluding. The results of this research indicate that madrasah development management is carried out by maximizing socialization to the community by face-to-face and the social media, by used three special programs, namely: 1) Arabic language guidance, 2) English language guidance, and 3) Extracurricular activities, and improving the productivity of independent madrasah business, namely cocoa farming; Management of Independent Business Development at Madrasah Aliyah As'adiyah No.16 Pengkendekan Sabbang District, North Luwu Regency is carried out by expanding the scope of business or business diversification, namely by developing new types of business in new business areas; and Management of Development of Madrasah Aliyah As'adiyah. This research implies that it is necessary to maximize the development of Madrasah with independent business to produce quality graduates in Islamic religious knowledge and entrepreneurship.